2014
DOI: 10.1111/bjop.12073
|View full text |Cite
|
Sign up to set email alerts
|

Serial killers, spiders and cybersex: Social and survival information bias in the transmission of urban legends

Abstract: . (2015) 'Serial killers, spiders and cybersex : social and survival information bias in the transmission of urban legends.', British journal of psychology., 106 (2). pp. 288-307. Further information on publisher's website: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
100
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(119 citation statements)
references
References 62 publications
(85 reference statements)
5
100
1
Order By: Relevance
“…Transmission chain studies have shown that certain kinds of information are preferentially transmitted. A result replicated by several independent labs is that information about social relationships is transmitted with higher fidelity than equivalent non-social information (McGuigan and Cubillo 2013; Mesoudi et al 2006;Reysen et al 2011;Stubbersfield et al 2014), as predicted by social brain theories of the biological evolution of primate cognition (Dunbar 2003). There is also experimental support for a bias for emotionally salient disgust-inducing information (Eriksson and Coultas 2014;Heath et al 2001).…”
Section: Cognitive Biases Can Drive Cultural Evolution Towards Culturmentioning
confidence: 91%
“…Transmission chain studies have shown that certain kinds of information are preferentially transmitted. A result replicated by several independent labs is that information about social relationships is transmitted with higher fidelity than equivalent non-social information (McGuigan and Cubillo 2013; Mesoudi et al 2006;Reysen et al 2011;Stubbersfield et al 2014), as predicted by social brain theories of the biological evolution of primate cognition (Dunbar 2003). There is also experimental support for a bias for emotionally salient disgust-inducing information (Eriksson and Coultas 2014;Heath et al 2001).…”
Section: Cognitive Biases Can Drive Cultural Evolution Towards Culturmentioning
confidence: 91%
“…These include: i) a bias for survival-relevant information, such as predators, the location of food, access to resources, reproductive strategies (e.g. Stubbersfield, Tehrani, & Flynn, 2015); ii) a bias for social information, e.g. about peoples' relations and interactions with one another (e.g.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…about peoples' relations and interactions with one another (e.g. Mesoudi, Whiten, & Dunbar, 2006;Stubbersfield, Tehrani, & Flynn, 2015); iii) a bias for emotionally arousing content, such as disgust, or amusement (Eriksson & Coultas, 2014;Stubbersfield, Tehrani, & Flynn, 2017); iv) a bias for minimally-counterintuitive (MCI) information that violates some of our implicit ontological assumptions about the world in ways that makes it more salient than information that can either be taken-for-granted or is incomprehensible (e.g. Barrett & Nyhof, 2001); v) a stereotype-consistency bias, in which information is transformed and recalled in ways that make it more consistent with pre-existing expectations and prejudices (e.g.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Selection-like "content" or "direct" biases favor the acquisition and transmission of some cultural variants over others due to their memorability or effectiveness (14,15), just as some alleles have higher fitness than others. Random cultural "mutation" occurs where new variation arises randomly, such as via perceptual error (16), akin to random genetic mutation.…”
Section: Cultural Microevolutionmentioning
confidence: 99%